Peningkatan Pengetahuan Gizi Siswa Kelas 5 SD ABATA Islamic School tentang Keamanan Makanan Jajanan - Ratnayani Ratnayani; Gusti Kumala Dewi; Vera Kasmira; Ina Ratnawati (Jurnal Abdimas Kesehatan (JAK), 2021)
An Elementary school (SD) children are one of the main targets of street food vendors. These snacks provide energy and some nutrients for those who consume it. However, there are things to be alert  from street food, especially in terms of food safety. There are still many street food that made using food additives (colourings, sweeteners, preservatives, etc.) that do not meet the requirements. This can cause poisoning and even Extraordinary Events. Based on this, it is necessary to provide education about street food for elementary school children so that they can choose the healthy street food. Given the unfavorable situation, education is conducted online through Google Meet (Gmeet). The theme raised in this education is "Great Children Have Healthy Snacks" and the targets are 5th graders at ABATA Islamic School Elementary School, Karawang. The education event was carried out twice, on January 14 and 21, 2021. To find out whether the participants had understood the material presented, a pre-test and post-test were conducted. This activity has increased students' nutritional knowledge. This can be seen from the average post-test score which is higher than the pre-test